Classroom Peer Effects and Student Achievement - Burke, Mary A.; Sass, Tim R. (Journal of Labor Economics, 2013)
We analyze the impact of classroom peers' ability (measured by their individual fixed effects) on student achievement for all Florida public school students in grades 3-10 over a 6-year period. We control for both student and teacher fixed effects, thereby alleviating biases due to endogenous assignment of both peers and teachers. Under linear-in-means specifications, estimated peer effects are small to nonexistent, but we find some sizable and significant peer effects within nonlinear models. We also find that classroom peers, as compared with the broader group of grade-level peers at the same school, exert a greater influence on individual achievement gains.